PROBLEMS AND PROSPECTS OF REPRODUCTION OF WORKING CAPITAL - Taigib Musaev (Вестник Северо-Кавказского федерального университета)
The article considers problems of reproduction of working capital. Studied in detail the preconditions which depend on the degree of financial support the current activities of the enterprises of agrarian sphere. Righteous analysis of the reproduction of working capital in the agricultural enterprises of the Republic of Dagestan over the past seven years. The prospects of solving the problems are studied with consideration of the peculiarities of transformation of current assets at different cycles of economic activity. Recommended on the basis of complex analysis of financial factors, the concept of reproduction of working capital will allow to identify potential to accelerate turnover and reduce working capital requirements as a whole. The optimal combination of own and borrowed sources of working capital it is important to take into consideration the inflation risks.